UPAYA PEMBIBITAN BIJISARANG SEMUT(Myrmecodiapendans) DENGAN KULTUR JARINGAN - Heru Sudrajad (Agriekonomika, 2012)
ABSTRAKRecently, to meet the needs of botanicals medicinal plants from the cultivation require good quality and uniform seeds on form and time. Thereby, study of anthill plant breeding (Myrmecodia pendans) with the provision of IBA and BAP through tissue culture is necessary.Tissue culture techniques has advantages because it is not affected by the climate, relatively fast production, free contamination of microbial and do not require large tracts of land. The study was conductedin a laboratorytissue cultureCentral Research andDevelopment ofMedicinal Plantsand Traditional MedicineTawangmangu. Research carried out byadding agrowth regulatorIBAandBAPeach withconcentrations0,2, 4and 6mg/l. The best result obtained  on treatment of  adding IBA and BAP 2 mg/ l during 2 months. It’s indicated by sum of leaf are 2, sum of root are 2 and length of root are 4 mm.Keywords: (Myrmecodia pendans) tissue culture, IBA BAP.